The dynamics of the scavenger profession: Economic motivation, social integration, and sustainability - Umarul Faruq; Subairi; Fatoni, Ihlasul (Alkasb: Journal of Islamic Economics, 2025)
Indonesia’s waste management crisis, being one of the world’s largest contributors of solid waste, highlights the strategic importance of the informal sector, particularly scavengers, who supply more than 80% of recyclable materials yet continue to face social stigma and systemic marginalization. This study examines the motivation and sustainability of the scavenger profession at the Angsanah Landfill (TPA) in Pamekasan, a distinctive context where scavengers experience full social integration without discrimination. Guided by Rational Choice Theory and Economic Behavior Theory, this research adopts a qualitative phenomenological approach. Data were collected through in-depth interviews with seven active scavengers, landfill managers, and village authorities, supported by field observation and documentation. The findings show that scavengers choose this occupation based on rational economic considerations; the prospect of relatively high earnings (up to IDR 2.8 million per month), low entry barriers, and flexible working hours. Socially, they benefit from strong community integration and the absence of negative stigma, which contrasts sharply with conditions commonly reported in major urban landfills. Despite these advantages, the long-term sustainability of the profession is threatened by increasing upstream waste-sorting initiatives, which significantly reduce the volume of recyclable waste that reaches the landfill. The study calls for policy interventions aimed at formalizing scavenger organizations through cooperatives, strengthening social protection, and integrating scavengers into circular economy frameworks, while considering the unique socio-cultural context of local communities to ensure inclusive and sustainable waste governance.